Response to Drought Stress of In Vitro and In Vivo Propagated Physalis peruviana L. Plants Inoculated with Arbuscular Mycorrhizal Fungi - Maria Geneva; Marieta Hristozkova; Elisaveta Kirova; Mariana Sichanova; Ira Stancheva (Agriculture, 2023)
Physalis peruviana L. is one of the most favorable tropical fruit due to its fast growth and nutritional properties. The current research outlined the response to drought stress of golden berry plants inoculated with arbuscular mycorrhizal fungi Claroideoglomus claroideum and propagated in vitro as well as from seeds. The implementation of mycorrhizal symbiosis was determined by root colonization, glomalin content, and alkaline and acid phosphatases in roots and soil. The plant protection was assured by enzyme and non-enzyme antioxidants. The adapted in vitro propagated plants demonstrated higher resistance to drought than plants developed from seeds indicated by increased growth parameters (shoot, root biomass, fruit number), plastid pigment content, antioxidant activity, and less enhance mentofoxidative markers levels in water-deficient conditions. The findings in the present research are relevant to obtain the optimal mycorrhizal association and type of propagation in an adverse environment for golden berry development and will lead to the establishment of a database and model of varied plant responses to stressful conditions such as drought.